Mestrados Profissionais em Ensino de Ciências: análise de dissertações e produtos educacionais sobre educação ambiental (2010-2019) - GOMES, Ana Samile Alves (2022)
The present study investigated the Professional Masters dissertations in Science Teaching, from 2010 to 2019, with a focus on the subject of EA, with an interdisciplinary approach in high school. The investigation consists of a bibliographic research, of the “State of the Art” type, of a quali / quantitative nature. A total production of 1017 dissertations was found. The analysis of the descriptor “Content / curricular theme’’, showed that the theme of EA presented 156 works from all levels of education, demonstrating that EA is important among the grouped themes. 32 dissertations aimed at EA-interdisciplinary-EM were cataloged. The descriptor Didactic-Methodological Resource, we highlight six categories found. The strategies adopted by the MP teachers are configured as systematic and innovative practices aimed at improving teaching. Such analysis will make it possible for the MP's products on EE to arrive as important didactic tools, both in the initial and continuing education of teachers, as well as in teaching practices in schools.